Psychometric Evaluation of the Academic Resilience Scale (ARS-30) in Iran - Alireza Ramezanpour; Maryam Kouroshnia; Amirhoushang Mehryar; Hojatalah Javidi (Iranian Evolutionary Educational Psychology Journal, 2019)
Over the past two decades, academic resilience has encouraged a great deal of research. However, there is a clear shortage of suitable standard tools for assessing academic resilience in Iran. The purpose of this study was to investigate the validity and reliability of the Academic Resilience Scale (ARS-30) in Iran. For this aim, 409 high school students (202 girls and 207 boys) completed the Academic Resilience Scale and self-regulation scale. Criterion validity analysis showed that there is a correlation between academic resilience scale and academic self-regulation. The results of factor analysis of the content of the scale in terms of principal components revealed there are three factors i.e. Represents Perseverance, Reflecting and Adaptive Help-seeking, and Negative Affect and Emotional Response. Internal consistency analysis showed that items related to each factor had the most significant correlation with the total score of that factor. There was also a significant correlation between the scores for each factor and the total score. The reliability of this scale was calculated by Cronbach's alpha coefficient and test-retest method. Generally, the results showed that the academic resiliency scale has good psychometric properties and can be used as a valid and reliable tool for Iranian students.